Redistribution without structural change in Ecuador: Rising and falling income inequality in the 1990s and 2000s - Juan Ponce; Rob Vos (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
This study examines the rise and fall in income inequality in Ecuador over the past two decades. Falling income equality during the 2000s partly coincides with the rise to power of a new leftist government, but the trend was already set early in the decade. The recent trend is mainly associated with a recovery from the country's deep crisis of the late 1990s. The new leftist regime's social transfer policies helped reduce inequality further, but the continuation of Ecuador's primary export-based growth model and the lack of structural economic change do not augur for a more structural decline in inequality.
Keywords: I240; I310; I390; 330; education; welfare; poverty; Ecuador; Einkommensverteilung; Einkommensumverteilung; Ecuador